Functional composition of epifauna in the south-eastern North Sea in relation to habitat characteristics and fishing effort. (5th February 2016) - Neumann, Hermann; Diekmann, Rabea; Kröncke, Ingrid
Abstract: Analysis of ecosystem functioning is essential to describe the ecological status of ecosystems and is therefore directly requested in international directives. There is a lack of knowledge regarding functional aspects of benthic communities and their environmental and anthropogenic driving forces in the southern North Sea. This study linked functional composition of epibenthic communities to environmental conditions and fishing effort and investigated spatial correlations between habitat characteristics to gain insight into potential synergistic and/or cumulative effects. Functional composition of epifauna was assessed by using biological trait analysis (BTA), which considered 15 ecological traits of 54 species. Functional composition was related to ten predictor variables derived from sediment composition, bottom temperature and salinity, hydrodynamics, annual primary production and fishing effort. Our results revealed significantly different functional composition between the Dogger Bank, the Oyster Ground, the West and North Frisian coast. Mobility, feeding type, size and adult longevity were the most important traits differentiating the communities. A high proportion of trait modalities related to an opportunistic life mode were obvious in coastal areas especially at the West Frisian coast and in the area of the Frisian Front indicating disturbed communities. In contrast, functional composition in the Dogger Bank area indicated undisturbed communities with prevalence of large, long-lived and permanently attached species being sensitive towards disturbance such as fishing. Tidal stress, mud content of sediments, salinity, stratification and fishing effort were found to be the most important habitat characteristics shaping functional composition. Strong correlations were found between variables, especially between those which changed gradually from the coast to offshore areas including fishing effort. Unfavourable extremes of these factors in coastal areas resulted in disturbed epibenthic communities, while the relative influence of a single factor on functional composition cannot be quantified. Coastal communities seemed to be well adapted to disturbance and the prevalence of opportunistic trait modalities not necessarily revealed a poor ecological status according to the Marine Strategy Framework Directive (MSFD). The integration of functional aspects into the assessment of ecosystem health is recommended, since widely used structural measures failed in naturally disturbed habitats.